On Strong Convergence of Halpern’s Method Using Averaged Type Mappings - F. Cianciaruso; G. Marino; A. Rugiano; B. Scardamaglia (Journal of Applied Mathematics)
Under suitable hypotheses on control coefficients, we study Halpern’s method to approximate strongly common fixed points of a nonexpansive mapping and of a nonspreading mapping or a fixed point of one of them. A crucial tool in our results is the regularization with the averaged type mappings.